New techniques: a roadmap for the development of HCC immunotherapy - Jiang, Dizhi; Ma, Xinyue; Zhang, Xun; Cheng, Bo; Wang, Ruiqing; Liu, Yuan; Zhang, Xinyu (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide. The absence of effective early diagnostic methods and the limitations of conventional therapies have led to a growing interest in immunotherapy as a novel treatment approach for HCC. The liver serves as an immune organ and a recipient of antigens from the digestive tract, creating a distinctive immune microenvironment. Key immune cells, including Kupffer cells and cytotoxic T lymphocytes, play a crucial role in HCC development, thus offering ample research opportunities for HCC immunotherapy. The emergence of advanced technologies such as clustered regularly interspaced short palindromic repeats (CRISPR) and single-cell ribonucleic acid sequencing has introduced new biomarkers and therapeutic targets, facilitating early diagnosis and treatment of HCC. These advancements have not only propelled the progress of HCC immunotherapy based on existing studies but have also generated new ideas for clinical research on HCC therapy. Furthermore, this review analysed and summarised the combination of current therapies for HCC and the improvement of CRISPR technology for chimeric antigen receptor T cell therapy, instilling renewed hope for HCC treatment. This review comprehensively explores the advancements in immunotherapy for HCC, focusing on the use of new techniques.